Leptin and melatonin’s effects on OVX rodents’ bone metabolism - Lin, Zhenen; Yu, Guanshu; Xiong, Shengren; Lin, Yu; Li, Zhaohui (Frontiers in Endocrinology, 2023)
Abstract Purpose: This study aims to examine the effects of leptin and melatonin intervention on bone metabolism in ovariectomize (OVX) rodents, as well as their potential mechanisms of action. Methods: Prepare an OVX model of osteoporosis in rodents and validate the model by collecting bilateral tibia samples for Micro-CT scanning and histological analysis.A control group of normal size, the OVX group, the OVX+Sema4D(Semaphorin 4D) group, the OVX+Sema4D+Leptin group, the OVX+Sema4D+ Melatonin(MT) group and the OVX+Sema4D+Leptin+ MT group were the experimental groups. Adenovirus vector construction and tibial medullary injection validation were conducted in accordance with the aforementioned experimental groups. Four groups of rats were injected with the Sema4D overexpression adenovirus vector into the tibial medullary cavity, and two groups were injected with the Leptin overexpression adenovirus vector. The repair of osteoporosis was observed using micro-CT and histological analysis.Immunohistochemical detection of bone morphogenetic protein-2 (BMP-2) expression in bone tissue was employed to ascertain the amount of osteoclasts in the upper tibial metaphysis, utilizing TRAP(tartrate-resistant acid phosphatase) staining. Results: Increased levels of BV/TV, Tb.N, BMD, and BMC were seen in the OVX+ Sema4D+Leptin, OVX+ Sema4D+MT, and OVX+ Sema4D+Leptin+ MT groups compared to the OVX group, whereas Tb. Sp levels were lowered. When compared to the Sema4D overexpression group, the trabecular bone structure of the OVX + Sema4D + Leptin, OVX + Sema4D + MT, and OVX + Sema4D + Leptin + MT groups is largely intact, tends to be closer, and the amount of trabecular bone increases. The OVX + Sema4D + Leptin + MT group in particular.The expression of BMP-2 was dramatically upregulated (p<0.05), the number of TRAP-stained osteoclasts was significantly reduced (p<0.05), and BALP(bone-derived alkaline phosphatase) and TRAP-5b(tartrate-resistant acid phosphatase-5b) activities were significantly downregulated (p<0.05). Conclusion: In rats with osteoporosis, leptin and melatonin can be seen to augment the trabecular microstructure of the bone, augment bone growth, diminish trabecular harm, and mend the bone. The combined effect is more powerful.